Low- or high-carbohydrate diet for athletes? - Zydek, G.; Michalczyk, M.; Zajac, A.; Latosik, E. (Trends in Sport Sciences, 2014)
The paper addresses the issue of selection of nutritional strategies, i.e. low- or high-carbohydrate diets, for athletes. On the basis of recent research the authors discuss in detail both dietary models and present their advantages and disadvantages. The paper includes practical implications and one-day low- carbohydrate and high-carbohydrate sample menus.